1970
DOI: 10.37090/jfl.v8i2.149
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Knowledge and Attitude Toward Behavior of Antibiotic Usage on Society in Talang Jawa Health Center of South Lampung August Period 2019

Abstract: In developing countries, many antibiotics are used without a doctor's prescription, causing someone to use antibiotics incorrectly. Lack of knowledge about antibiotics is a major factor that triggers an increase in the rate of bacterial resistance to antibiotics. Knowledge and attitude become one of the social cognitive factors that influence antibiotic use behavior.This study aims to determine the relationship of knowladge and attitudes toward of antibiotic usage behavior in community of Talang jawa public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was discussed by Valois et al [28] that people with more negative effects on themselves adopt more adaptive behaviors during flood events. It is established by a vast list of behavioral principles that tie behavior to a wide range of outcomes and other qualities [29]. In a study by Huang et al [24] in Shenzhen, China, the sole direct factor that influences individual coping behavior is flood risk attitude.…”
Section: Hypothesis 12 (H12)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was discussed by Valois et al [28] that people with more negative effects on themselves adopt more adaptive behaviors during flood events. It is established by a vast list of behavioral principles that tie behavior to a wide range of outcomes and other qualities [29]. In a study by Huang et al [24] in Shenzhen, China, the sole direct factor that influences individual coping behavior is flood risk attitude.…”
Section: Hypothesis 12 (H12)mentioning
confidence: 99%
“…A self-administered questionnaire (SAQ) is a questionnaire designed to be completed by a respondent without the assistance of the researchers for the collection of data [40]. This questionnaire is developed based on the related literature [3,16,17,19,22,23,25,28,29,39, followed by the conceptual research framework containing the hypotheses of the study discussed in the previous chapter. The research identified in Table 2 was used to identify the factors that influence flood disaster preparedness and mitigation in flood-prone areas in the Philippines, with the integration of Protection Motivation Theory (PMT) and Theory of Planned Behavior (TPB).…”
Section: Questionnairementioning
confidence: 99%